2019
DOI: 10.12688/wellcomeopenres.15298.1
|View full text |Cite
|
Sign up to set email alerts
|

A realist review of community engagement with health research

Abstract: Introduction: Community engagement is increasingly recognized as a critical aspect of global health. Recent years have seen an expansion of community engagement activities linked to health research, but debates and inconsistencies remain about the aims of different types of engagement, mechanisms underpinning their implementation and impact, and influential contextual factors. Greater commitment to and consistency around community engagement by health research programs, implementers and funders requires a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…15 17 Insights from micro-level and meso-level are important for informing change at the macro-level where policies are formulated and decided 16 ; and for generating community awareness and ownership of solutions for improving healthcare access. 17…”
Section: Conceptualising Access In Contextmentioning
confidence: 99%
“…15 17 Insights from micro-level and meso-level are important for informing change at the macro-level where policies are formulated and decided 16 ; and for generating community awareness and ownership of solutions for improving healthcare access. 17…”
Section: Conceptualising Access In Contextmentioning
confidence: 99%
“…A systematic review found that it is a concept that is rarely explicitly named in abstracts and titles and rarely engaged with; lack of acknowledgement of its existence could be holding back discovery within this field. [63][64][65][66][67][68][69][70][71][72][73][74] Programme theory A resultant programme theory was produced following the five steps shown in figure 4. The programme theory informed discussions with stakeholders to develop recommendations and actions (table 1) for individuals, organisations, institutions and policymakers to improve the informed consent process.…”
Section: Organisational and Individual Cultural Competencymentioning
confidence: 99%
“…The broader outcomes of CE vary with the goals or purpose of the intervention in which it is incorporated [ 24 ]. CE has been used to enable community participation, protect communities’ interests, tailor programmes to a community’s needs, build capacity, and encourage programme acceptance [ 25 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent civil wars and the challenging process of rebuilding trustworthy structures of governance could explain, in part, the community resistance and mistrust that was common throughout the epidemic; this was also reflected in the approaches of CE during the response [ 13 , 32 , 39 – 41 ]. Existing relationships and social hierarchies, socioeconomic status, cultural beliefs and values, the state of the health system, and community perceptions and knowledge are all contextual factors to be considered in the development and implementation of CE strategies [ 13 , 22 , 24 , 32 , 35 , 37 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation